Study on clinical presentation and etiological profile of atrial fibrillation patients - Bashir Ahmed, Sayyed Amjad; M., Rudrakshi Siddheshwar; Aminsab, Bennishirur Wasim Ahmed (International Journal of Advances in Medicine, 2019)
Background: Atrial fibrillation is one of most common arrhythmias observed in general practice. Atrial fibrillation may occur paroxysmal or may become established as permanent condition. The aim of the treatment of atrial fibrillation is either normalization of rhythm by cardioversion or control of ventricular rate by drugs. The present work was undertaken to study, clinical presentation, aetiology and complications in patients developing atrial fibrillation. Methods: A prospective study carried out at Department of Medicine V.M. Medical college and Shri Chhatrapati Shivaji Maharaj Sarvopachar Rungnalaya, Solapur, over the study period of two years. 100 patients of atrial fibrillation diagnosed by following clinical and ECG criteria were included. Detail study of aetiology complication and clinical presentation of atrial fibrillation was done in present study. Results: Commonest presenting symptom was breathlessness (70%) followed by palpitation (58%). Common signs elicited were irregular pulse, apex pulse deficit (92%). Congestive cardiac failure was present in 46% patient among those raised JVP was seen in 100% cases, oedema in 60.8% hepatomegaly 63.04% basal crepitations in 86.9% cases. ECG revealed coarse fibrillary waves (81.8%) in patients with rheumatic heart disease whereas fine fibrillary waves were seen in patients with IHD as cause of AF. Conclusions: Size of fibrillary was may be predicted etiology of AF as coarse waves are common in rheumatic and fine waves in non- rheumatic AF. The present paper would help in early diagnosis and prompt treatment of AF.